Ionic liquid based in situ solvent formation microextraction followed by on-line phase separation coupled with cold vapor-atomic absorption spectrometry for mercury determination in seafood samples. Issue 35 (24th August 2017) - Molaei, Saeideh; Seidi, Shahram; Saleh, Abolfazl; Ghoulipour, Vanik
Abstract : Ionic liquid based in situ solvent formation microextraction followed by on-line phase separation coupled with CV-AAS for mercury analysis. Abstract : Ionic liquid based in situ solvent formation microextraction (IL-ISFME) followed by on-line phase separation coupled to cold vapor-atomic absorption spectrometry (CV-AAS) was introduced based on using a homemade in-line filter for phase separation. In this method, low cost and easy to access PTFE powder, as an industrial raw material, was used to fill a medical syringe and applied for the separation of hydrophobic ionic liquid containing analytes. The developed methodology is simple and eliminates the application of centrifugation in the phase separation step to overcome some limitations of emulsification techniques. In IL-ISFME an ion-pairing agent was added to a sample solution containing hydrophilic IL. In the following, the fine droplets of hydrophobic IL made by the promotion of a metathesis reaction were recovered via an in-line filter. To show the applicability of the proposed method, it was applied for the extraction and determination of mercury in seafood samples. The effects of some important parameters were investigated and optimized using a central composite design (CCD). Under the optimized conditions, the linearity of the method was obtained over a range of 2–200 μg L −1 with a determination coefficient ( R 2 ) higher than 0.996. The enrichment factor (EF) and absolute recovery (AR%) of the method achieved were 5.7 and 57.3%, respectively. The limits of detection (LOD) and quantification (LOQ) were found to be 0.6 and 2.0 μg L −1 respectively. The intra- and inter-day precisions expressed as relative standard deviations (RSD%, n = 3) were 4.8% and 7.6%, respectively. The relative recoveries (RR%) obtained were in the range of 80 to 90.5%, which correspond to the relative errors of −20% to −9.5%, respectively, confirming the achievement of satisfactory accuracies by the proposed procedure.